Managers’ Perceptions of Exports Problems and Assistance Requirements: An Investigation into the Effect of Ethnicity - Dave Crick; Shiv Chaudhry (Asian Academy of Management Journal, 1997)
Managers’ Perceptions of Exports Problems and Assistance Requirements: An Investigation into the Effect of Ethnicity (PDF not available)